Safe Food Practices among the Regimental Food Handlers of Selected Military Unit (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Food safety is a key public health concern. Food handlers play an important role in ensuring food safety throughout the chain of preparation, storage and serving.Aim: To assess the food safety practice level among the food handlers of selected unit messes in Dhaka Cantonment.Methods: This descriptive cross sectional study was conducted among the food handlers of selected unit messes in Dhaka Cantonment from January 2013 to December 2013. A total of 133 food handlers were selected following convenient sampling technique. Data were collected by face to face interview using a predesigned semi-structured questionnaire and check list. All completed questionnaires were validated manually and data were analyzed with Statistical Package for the Social Sciences (SPSS) verson 15.0 by using descriptive and inferential statistics.Results: In this study, the food handlers had a mean age of 32.94 years; all were male and Muslim. Regarding educational qualification, majority (42.9%) were between class VI to X and 80.5% were married. The mean monthly income of the participants was taka 17,115.8 and 53.4% belonged to nuclear family. Majority (65.4%) of the participants were cook and 39.8% had family members between 4-5 persons. It was found that out of all food handlers 12% had good, 78.9% had average and 9.0% had poor food safety practice status. Descriptive statistics revealed that occupation, education and marital status played a major role for food safety practice level.Conclusion: Efforts need to be taken to improve the awareness among the food handlers. Safety practices and further studies are recommended on determinants of non-compliance to safety practices by the food handlers.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 65-68